The Arabs and the Holocaust : the Arab-Israeli war of narratives - Achcar, Gilbert; Goshgarian, G. M. (London Saqi Books, 2011)
Considers conflicting Middle-East perspectives on the Holocaust, analyzing such topics as Arab responses to Nazism, the creation of Israel, and the destruction of Palestine.
Part I: The Time of the Shoah --  Arab Reactions to Nazism and Anti-Semitism, 1933-47 --  Part I. The Liberal Westernizers --  2. The Marxists --  3. The Nationalists --  4. Reactionary and/or Fundamentalist Pan-Islamists -- Part II: The Time of Nakba --  Arab Attitudes to the Jews and the Holocaust from 1948 to the Present --  5. The Nasser Years (1948-67) --  6. The PLO Years (1967-88) --  7. The Year of the Islamic Resistances (1988 to the Present) --  Conclusion: Stigmas and Stigmatization
Originally published in France by Actes Sud as Les arabes et la Shoah
Includes bibliographical references and index
Keywords: History; HOLOCAUST; PUBLIC OPINION; NATIONALISM; JEWS; ARABS